2019
DOI: 10.2460/ajvr.80.11.1001
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two inhibitors of E-type prostanoid receptor four and carprofen in dogs with experimentally induced acute synovitis

Abstract: OBJECTIVE To investigate the ability of a proprietary antagonist of E-type prostanoid receptor (EP) 4, grapiprant, and carprofen to attenuate lameness attributable to urate-induced synovitis in dogs. ANIMALS 5 purpose-bred hound-cross dogs. PROCEDURES A blinded, 3-way crossover study was performed. Dogs received each of 3 treatments (L-766, a proprietary antagonist of EP4; 4.0 mg/kg), grapiprant (an antagonist of EP4; 2.0 mg/kg), and carprofen (4.4 mg/kg); dogs received 4 doses of each treatment (14 and 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 30 publications
2
17
0
Order By: Relevance
“…The ability of a proprietary antagonist of the EP 4 receptor (4 mg/kg), grapiprant (2 mg/kg) and carprofen (4.4 mg/kg) to attenuate lameness attributable to urate‐induced synovitis was investigated in five dogs (Budsberg et al, 2019 ). Measurements of vertical ground reaction forces and clinical lameness scores were used to assess the analgesic activities of the different compounds.…”
Section: Pharmacodynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ability of a proprietary antagonist of the EP 4 receptor (4 mg/kg), grapiprant (2 mg/kg) and carprofen (4.4 mg/kg) to attenuate lameness attributable to urate‐induced synovitis was investigated in five dogs (Budsberg et al, 2019 ). Measurements of vertical ground reaction forces and clinical lameness scores were used to assess the analgesic activities of the different compounds.…”
Section: Pharmacodynamicsmentioning
confidence: 99%
“…Grapiprant is a newly introduced drug, and so reports of testing under laboratory and field conditions have been limited to studies that are required for regulatory approvals (Rausch‐Derra, Huebner, et al, 2016 ). Surprisingly two experimental (Budsberg et al, 2019 ; de Salazar Alcalá et al, 2019 ) studies show that grapiprant, a drug with presumptive advantages, has less efficacy than established treatments. It should be noted that the experimental animal model used (intra‐articular injection of sodium urate in the stifle joints of dogs) produces acute pain while grapiprant is approved for chronic pain.…”
Section: Pharmacodynamicsmentioning
confidence: 99%
“… Model Large animals Key features Rodent equivalent? (Y/N) Naturally occurring arthritis Horse ( Coppelman et al, 2019 , Mariñas-Pardo et al, 2018 ; C. W. McIlwraith et al, 2012 ; Pujol et al, 2018 )Dog ( Alves et al, 2020 , Carter et al, 1999 , Malek et al, 2020 , Moreau et al, 2014 , Riley et al, 2016 )Pig ( Kreinest et al, 2016 , Macfadyen et al, 2019 )Monkey ( Carlson et al, 1994 , Rothschild et al, 1997 ) Behavior: Clinical signs of lamenessAppearance: Inflamed (for inflammatory arthritis)Pathology: anterior cruciate ligament deficiency; cartilage erosion; synovium thickening and fibrosis; osteophytes formation; subchondral bone thickening and neovascularisationMolecular: Proteoglycans and type II collagen loss in cartilage N, but occurs in transgenic animals ( Christensen et al, 2016 , Staines et al, 2017 ) Degeneration-focused models of arthritis Monosodium Iodoacetate (MIA) induced arthritis Pig ( Uilenreef et al, 2019 , Unger et al, 2018 )Dog ( Budsberg et al, 2019 , Goranov, 2012 , Pomonis et al, 2018 ) Behavior: Lameness; increased asymmetric weight bearing;Pathology: cartilage necrosis and discoloration; synovial membrane thickening; subchondral bone necrosisMolecular: Increased pro-inflammatory cytokine expression profile in synovium Y ( Harvey and Dickenson, 2009 , Udo et al, 2016 ) Osteochondral chip fragment model Horse ( Broeckx et al, 2019 , Frisbie et al, 1997 , Knych et al, 2017 ) Behavior: LamenessPathology: Subintimal hyperplasia and fibrosisMolecular: Inflammatory genes expression change in synovial fluid; structural genes (collagen and aggrecan) expression change in cartilage N Osteochondral/Chondral defect induced arthritis Horse ( Niemelä et al, 2019 , Salonius et al, 2019 ...…”
Section: Limitations Of Large Animal Researchmentioning
confidence: 99%
“…Among chemically induced OA models, MIA injection into the joint is most commonly used and acts by inhibiting glyceraldehyde-3-phosphate dehydrogenase (GAPDH, an enzyme involved in glycolysis), which leads to the death of chondrocytes and has proven useful for understanding OA pain mechanisms ( Combe et al, 2004 , Samvelyan et al, 2020 ). The MIA model of OA has been successfully induced in pigs and dogs, as evidenced by both lameness and structural changes in the joints being observed in these animals following MIA administration ( Budsberg et al, 2019 , Uilenreef et al, 2019 ). Joint damage models, for example osteochondral fragment models, are well described in the horse, whereas destabilization of the joint is more commonly described in ruminant and dog models.…”
Section: Naturally Occurring and Models Of Arthritis In Large Animalsmentioning
confidence: 99%
“…7,8 The purpose of the study reported here was to examine the ability of AC to attenuate lameness attributable to SU-induced synovitis in the stifle joint of dogs and to compare those effects with the effects of an NSAID (carprofen) known to successfully attenuate signs of lameness in dogs that have this experimental condition. [9][10][11][12][13] Measurement of plasma concentrations of the administered drugs was included in the protocol to ensure that the drugs had been administered in accordance with the protocol and had achieved measurable plasma drug concentrations. Intra-articular SU injection induces a consistent self-limiting lameness and provides a predictable method for detecting changes in lameness associated with transient inflammatory synovitis over a moderate period (36 to 48 hours).…”
Section: Conclusion and Clinical Relevancementioning
confidence: 99%